(untitled) (American Journal of Technology and Applied Sciences, 2025)
This study examines the application of quality management principles to poverty reduction strategies in regional development. Traditional poverty alleviation programs often focus on financial assistance and social welfare, but the integration of quality management—particularly approaches derived from Total Quality Management (TQM), Six Sigma, and continuous improvement—offers sustainable and measurable results. The paper argues that poverty reduction efforts can become more efficient when quality-based planning, stakeholder engagement, and performance monitoring are embedded in governance systems. The research suggests that quality management frameworks enhance policy effectiveness, accountability, and the alignment of resources with community needs.